Analisis Wacana Kritis Model Teun A. van Dijk pada Surat Kabar E-Paper Harian Analisa dengan Tajuk “Citayam Fashion Week Kaum Muda Pinggiran, Duta Local Pride” - Tarida Alvina Simanjuntak; Marlina Agkris Tambunan; Natalina Purba; Juni Agus Simaremare; Nanda Ayu Safira (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This study aims to describe the editorial of “Citayam Fashion Week Young People, Local Pride Ambassadors as seen from the critical discourse theory of Teun A.Van Dijk in newspapers. The method used is descriptive method. The results obtained in this study are that there are 3 macro structures, namely 1 delection, 1 selection, 1 integration or construction. The title also has 2 superstructures consisting of titles, leads and story schemes consisting of situations and comments. The results of this study also have a micro structure (semantics) which consists of the background. details, intentions, and presuppositions. Microstructure II (syntax) consists of active and passive sentences, the use of distinguishing and contrasting coherence, and third person plural pronouns. Microstructure III (stylistic) consists of foreign language vocabulary that is currently widely used, microstructure IV (rhetorical) in this heading consists of graphics, metaphors, and expressions. This research is expected to be a reference for future researchers.